Assessing Institutional Performance in Private ‎Schools in Hodeidah City Using the ‎Balanced ‎Scorecard (BSC) from the Perspective of Principals,‎ ‎Deputy Principals and Teachers - Al-Amery, Abdulaziz (Jordan Journal of Educational Sciences, 2022)
This study aimed to assess the level of institutional performance in private schools in Hodeidah city using the Balanced Scorecard (BSC) as perceived by principals, deputy principals and teachers. The researcher adopted the descriptive analytical method and prepared a questionnaire consisting of 53 items. The study sample consisted of (215) respondents, 60 of whom were from the school leadership (principals, deputy principals) and 155 were teachers. The results of the study showed that the level of institutional performance in private schools in Hodeidah city according to the balanced scorecard perspective was generally moderate, with a mean value of (3.32). The domain of "internal processes" came in the first rank, with a mean value of (3.42), while the "financial" dimension came in the fourth and last rank, with a mean value of (3.21).The results also showed that there were no statistically significant differences at the level of significance (α =0.05) attributed to variables (gender, job title and years of service).